2020
DOI: 10.3390/mti4020020
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Gaze in Music. Leonard Bernstein’s Conducting Eyes

Abstract: The paper argues for the importance and richness of gaze communication during orchestra and choir conduction, and presents three studies on this issue. First, an interview with five choir and orchestra conductors reveals that they are not so deeply aware of the potentialities of gaze to convey indications in music performance. A conductor who was utterly conscious of the importance of gaze communication, however, is Leonard Bernstein, who conducted a performance of Haydn’s Symphony No. 88 using his face and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Since the project leverages an affordance of MHD's self-contained sensors and actuators as well as the computing power equivalent to personal computers, the article has a broad impact towards a possible scalability for enabling musical interactions for a larger audience. [91] is inspired by an extraordinary question: "…for the gaze communication system we use in everyday life, it is possible to write down a lexicon and an "optology", therefore, why not write down a lexicon of the conductor's gaze?" Such "why not" leads to the conception of experimental studies reported in this article.…”
Section: Musical Control Gestures In Mobile Handheld Devices: Design ...mentioning
confidence: 99%
“…Since the project leverages an affordance of MHD's self-contained sensors and actuators as well as the computing power equivalent to personal computers, the article has a broad impact towards a possible scalability for enabling musical interactions for a larger audience. [91] is inspired by an extraordinary question: "…for the gaze communication system we use in everyday life, it is possible to write down a lexicon and an "optology", therefore, why not write down a lexicon of the conductor's gaze?" Such "why not" leads to the conception of experimental studies reported in this article.…”
Section: Musical Control Gestures In Mobile Handheld Devices: Design ...mentioning
confidence: 99%
“…One is to focus on a single modality and to search for all the signals used by conductors in that modality. This has been done, for instance, for the conductor’s lexicon of gaze (Poggi, 2018; Poggi & Ansani, 2018; Poggi et al, 2020), where all the gaze items used in conduction were listed, whether conveying emotions, indications of intensity, pitch, or expressivity. Another route is to select a semantic area, among the meanings that conductors must convey, and to search for the signals of either one or all the modalities that provide indications in this area: for example, one could investigate the gestures of attack or closing.…”
Section: The Conductor’s Communication Systemsmentioning
confidence: 99%
“…Penelitian kondakting dilakukan oleh (Poggi et al, 2020) yang berpendapat tentang pentingnya kekayaan komunikasi tatapan selama melaksanakan kondukting orkestra dan paduan suara. Penelitian dilakukan terhadap Leonard Brenstein yang secara unik menggunakan ekspresi wajah dan tatapan saja ketika ia mengkondak pertunjukan Symphony No.88 karya Josep Haydn.…”
unclassified